Empirical Study on the Relationship Between the Internationalization of Vocational Education in Higher Vocational Colleges in Jilin Province and the International Competitiveness of Talents - Xiaoying, Li; Isa, Zainudin Bin Mohd (Journal of Advanced Research in Education, 2025)
With the development of globalization and Industry 4.0, the internationalization of vocational education has become an important way to enhance the international competitiveness of regional talents. As a typical cold-region border province in Northeast China, Jilin Province has made certain progress in the introduction of international courses, internationalization of teachers, and integration of industry certifications in higher vocational colleges. However, the overall level still lags behind advanced regions in China, which restricts the international adaptability of technical and skilled talents. Based on the theories of human capital and competitive advantage, this paper uses a combination of questionnaire surveys and semi-structured interviews to analyze the influence mechanism of international input and certification transformation in higher vocational colleges in Jilin Province on students’ knowledge transfer ability, cultural adaptability, and technical competitiveness, and puts forward corresponding countermeasures and suggestions. The research results show that the degree of internationalization and certification transformation have a significant positive effect on the international competitiveness of talents, and policy support and cross-cultural differences have a moderating effect on their influence. The research conclusions provide theoretical support and operational paths for the internationalization practice of vocational education in the cold regions of Northeast China.